2017
DOI: 10.1177/0194599817721688
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Synkinesis in Unilateral Vocal Fold Paralysis

Abstract: Objectives In patients with unilateral vocal fold paralysis (UVFP), laryngeal electromyography (LEMG) occasionally observes synkinesis in laryngeal muscles, a condition that could impair vocal fold mobility and voice control. This study aims to evaluate the impact of synkinesis on UVFP patients. Study Design A retrospective case-control study. Setting Medical center. Subjects and Methods Patients with UVFP onset >6 months were recruited (N = 104). The outcome measurements included LEMG, quantitative LEMG analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…5 LEMG performed during phonation and inspiration is the gold standard for diagnosing laryngeal synkinesis. 25 In the present study, preoperative LEMG findings indicated that TA muscle recruitment in all patients was mixed or full interference during a sniff and phonation with exertion, whereas TA recruitment during a sniff was greater than or equivalent to that during phonation with exertion, consistent with the definition of synkinesis provided by Maronian. 18 Preoperative video recordings also showed that the involved vocal cords were in the midline in 53.8% (7 of 13) of cases, found to be concave during quiet breathing, and showed bulging or paradoxical adduction during a sniff in 61.5% (8 of 13) of patients.…”
Section: Discussionsupporting
confidence: 87%
“…5 LEMG performed during phonation and inspiration is the gold standard for diagnosing laryngeal synkinesis. 25 In the present study, preoperative LEMG findings indicated that TA muscle recruitment in all patients was mixed or full interference during a sniff and phonation with exertion, whereas TA recruitment during a sniff was greater than or equivalent to that during phonation with exertion, consistent with the definition of synkinesis provided by Maronian. 18 Preoperative video recordings also showed that the involved vocal cords were in the midline in 53.8% (7 of 13) of cases, found to be concave during quiet breathing, and showed bulging or paradoxical adduction during a sniff in 61.5% (8 of 13) of patients.…”
Section: Discussionsupporting
confidence: 87%
“…With respect to the RLN, adductor and abductor axons are distributed within the nerve . With axonal regrowth, synkinetic reinnervation—misguided adductor and abductor regeneration—can occur . Although the LNW technique in the study promoted higher adductor recovery compared to microsuture repair, LNW may have also increased the rate of synkinetic adductor axon reinnervation to abductor muscles.…”
Section: Discussionmentioning
confidence: 99%
“…33 In this case, reinnervation could increase the CMAP amplitude; however, this may not render improved laryngeal function since a component of the reinnervation is synkinetic. 34 With some forms of iatrogenic injury, the RLN may be stretched during retraction resulting in neurapraxia 5 -typically causing a transient conduction block. 17 Following acute neurapraxia, stimulation of the RLN proximal to the injury site does not generate any CMAP amplitude, making determination between neurapraxia and complete transection difficult.…”
Section: Discussionmentioning
confidence: 99%
“…33 In this case, reinnervation could increase the CMAP amplitude; however, this may not render improved laryngeal function since a component of the reinnervation is synkinetic. 34…”
Section: Discussionmentioning
confidence: 99%